Interpersonal Attraction In Tess Gerritsen's Never Say Die (1992): A Social Psychological Perspective - Wahyuni, Sri (2012)
The objectives of the study are to analyze the structural element of the novel and the interpersonal attraction among the major characters in the novel based on social psychological perspective. This study is a qualitative study. The object of the study is Tess Gerritsen's Never Say Die published in 1992 in USA by Harlequin Books S.A. There are two data sources, namely primary data source and secondary data source. The primary data is the novel itself and the secondary is other sources such as the author biography, books of literary theory and also social psychology books. The method of collecting data is library research. The technique of data analysis is descriptive analysis. There are two results of the study. First, based on structural analysis of novel, it is clear that the author wants to convey her idea about love which can appear because of familiarity. In conveying her idea, Gerritsen creates and arranges her structural elements of novel be unity to support her idea. Second, based on the social psychological perspective, especially about interpersonal attraction, it is clear that Gerritsen illustrates a psychological phenomenon in which individuals can be attracted to one another because of familiarity.